Parents Experiences Using Alternative Medicine on Children Suffering Cancer in Jakarta - Hermalinda, Hermalinda; Rustina, Yeni; Novieastari, Enie (Universitas Airlangga, 2015)
Introduction: Alternative medicine are very popular today as a therapy that are believed to treat cancer. A phenomenology study was carried out to identify the experince of parentâs in using alternative medicine for children with cancer. Method: The method of data collection was indepth interview to eigth parents and data was analyzed by Colaiziiâs method. Themes of this research are the impact of illness to children, parentâs effort, description of alternative medicine, the effect of alternative medicine for children, meaning of using alternative medicine and parents expectation. Result: No benefit effect for children and detterence effect in using alternative medicine are current fi ndings in this research. Discussion: Healthcare professional should concerned about using alternative medicine in children and providing adequate information regarding effectiveness and adverse effects of alternative medicine. Keywords: parents experiences, alternative medicine, children with cancer